Electrochemiluminescent Properties of Organic Films with Incorporated Carbon Nanotubes - Yu.T. Zholudov; O.M. Bilash; M.M. Rozhitskii (Журнал нано- та електронної фізики)
This work describes the study of the electrochemical and electrochemiluminescent properties of electrodes modified by films of polyvinyl alcohol containing luminophor tris-bipyridine ruthenium and carbon nanotubes. Studied electrode structures showed good applicability for the development of nanotechnological ECL-sensors intended for the assay in aqueous mediums.